Bioproduction of Conjugated Linoleic Acid in Yogurt by Probiotic Bacteria - Khosravi-Darani, Kianoush; Reihani, Fatemeh Seyed; Feili, Reza (International Journal of Biotechnology for Wellness Industries, 2014)
Conjugated linoleic acid as unique fatty acid of milk fat has beneficial properties including antioxidant‚ anticarcinogen‚ antidiabetic‚ antiblood pressure‚ stimulating the body immune system and reducing cholesterol. The aim of this study was assessing ability of some probiotics for biotransformation of linoleic acid to conjugated linoleic acid. Effect of process variables were investigated on production of conjugated linoleic acid in probiotic yogurt. An 8 run Plackett-Burman design was used to study the effect of 7 variables included: addition of supplements (whey powder‚ the amount of added grape seed oil), fermentation (temperature, pH, incubation time) and inoculum condition (age and size) on biomass and conjugated linoleic acid production in probiotic yogurt containing strains of Lactobacillus acidophilus La5, Bifidobacterium bifidum and Propionibacterium freudenerchii grown in medium containing free linoleic acid. The highest amount of conjugated linoleic acid was obtained by addition of 8% w/v whey powder, addition of 4%v/v grape seed oil in pH=6.0, inoculation of 0.7%v/v Inoculum of 36 h age and fermentation at temperature of 35°C for 27 h. This research showed that at the optimized conditions‚ the amount of conjugated linoleic acid in probiotic yogurt was increased by 40% from an average of 8.01 mg/g fat in non-treated yogurt to 11.03 mg/g fat of probiotic yogurt containing grape seed oil.